 Dirac Slash
Get Dirac Slash essential facts below. View Videos or join the Dirac Slash discussion. Add Dirac Slash to your PopFlock.com topic list for future reference or share this resource on social media.
Dirac Slash

In the study of Dirac fields in quantum field theory, Richard Feynman invented the convenient Feynman slash notation (less commonly known as the Dirac slash notation). If A is a covariant vector (i.e., a 1-form),

${A\!\!\!/}\ {\stackrel {\mathrm {def} }{=}}\ \gamma ^{\mu }A_{\mu }$ using the Einstein summation notation where γ are the gamma matrices.

## Identities

Using the anticommutators of the gamma matrices, one can show that for any $a_{\mu }$ and $b_{\mu }$ ,

{\begin{aligned}{a\!\!\!/}{a\!\!\!/}&\equiv a^{\mu }a_{\mu }\cdot I_{4}=a^{2}\cdot I_{4}\\{a\!\!\!/}{b\!\!\!/}+{b\!\!\!/}{a\!\!\!/}&\equiv 2a\cdot b\cdot I_{4}\,\end{aligned}} .

where $I_{4}$ is the identity matrix in four dimensions.

In particular,

${\partial \!\!\!/}^{2}\equiv \partial ^{2}\cdot I_{4}.$ Further identities can be read off directly from the gamma matrix identities by replacing the metric tensor with inner products. For example,

{\begin{aligned}\operatorname {tr} ({a\!\!\!/}{b\!\!\!/})&\equiv 4a\cdot b\\\operatorname {tr} ({a\!\!\!/}{b\!\!\!/}{c\!\!\!/}{d\!\!\!/})&\equiv 4\left[(a\cdot b)(c\cdot d)-(a\cdot c)(b\cdot d)+(a\cdot d)(b\cdot c)\right]\\\operatorname {tr} (\gamma _{5}{a\!\!\!/}{b\!\!\!/}{c\!\!\!/}{d\!\!\!/})&\equiv 4i\epsilon _{\mu \nu \lambda \sigma }a^{\mu }b^{\nu }c^{\lambda }d^{\sigma }\\\gamma _{\mu }{a\!\!\!/}\gamma ^{\mu }&\equiv -2{a\!\!\!/}\\\gamma _{\mu }{a\!\!\!/}{b\!\!\!/}\gamma ^{\mu }&\equiv 4a\cdot b\cdot I_{4}\\\gamma _{\mu }{a\!\!\!/}{b\!\!\!/}{c\!\!\!/}\gamma ^{\mu }&\equiv -2{c\!\!\!/}{b\!\!\!/}{a\!\!\!/}\\\end{aligned}} where

$\epsilon _{\mu \nu \lambda \sigma }\,$ is the Levi-Civita symbol.

## With four-momentum

Often, when using the Dirac equation and solving for cross sections, one finds the slash notation used on four-momentum: using the Dirac basis for the gamma matrices,

$\gamma ^{0}={\begin{pmatrix}I&0\\0&-I\end{pmatrix}},\quad \gamma ^{i}={\begin{pmatrix}0&\sigma ^{i}\\-\sigma ^{i}&0\end{pmatrix}}\,$ as well as the definition of four-momentum,

$p_{\mu }=\left(E,-p_{x},-p_{y},-p_{z}\right)\,$ we see explicitly that

{\begin{aligned}{p\!\!/}&=\gamma ^{\mu }p_{\mu }=\gamma ^{0}p_{0}+\gamma ^{i}p_{i}\\&={\begin{bmatrix}p_{0}&0\\0&-p_{0}\end{bmatrix}}+{\begin{bmatrix}0&\sigma ^{i}p_{i}\\-\sigma ^{i}p_{i}&0\end{bmatrix}}\\&={\begin{bmatrix}E&-\sigma \cdot {\vec {p}}\\\sigma \cdot {\vec {p}}&-E\end{bmatrix}}.\end{aligned}} Similar results hold in other bases, such as the Weyl basis.